"Homeless" Deities and Refugee Devotees: Hindu Temples, Sri Lankan Tamil Diaspora, and Politics in the United Kingdom. Issue 3 (27th May 2021) - Maunaguru, Sidharthan
ABSTRACT: This article explores the role played by Hindu temples in Sri Lankan Tamils' lives in the diaspora in the United Kingdom. It investigates why those temples became not only places for religious worship but also hubs for the expression of Tamil nationalistic political views, while temples in Sri Lanka managed to keep those politics at bay. Departing from studies on religious belonging in the diaspora, I argue for the specificity of the Sri Lankan experience as mingled with the suffering of war and Tamil nationalistic politics, thus suggesting that historical and political processes are key to understand ways of belonging. I use the lens of the capacity of the sovereign deities to unravel the various ways employed by deities to cater to their devotees' needs. I explore how Hindu deities and refugee devotees in London, while accommodating nationalistic politics, try to establish their own power and claim a form of belonging in the new country. I argue that in the process, both the new sovereign deities and Tamil migrants/refugees not only need each other but also need the deities from home across time and space. [ politics, religion, sovereign deity, belonging, diaspora ] RESUMEN: Este artículo explora el rol desempeñado por los templos hindúes en las vidas de los tamiles de Sri Lanka en la diáspora en el Reino Unido. Investiga por qué esos templos llegan a ser no sólo lugares de culto religioso, sino también focos de expresión de puntos de vista políticos nacionalistas tamiles, mientras los templos en Sri Lanka lograron mantener a raya esos puntos de vista políticos. Apartándome de estudios sobre pertenencia religiosa en la diáspora, argumento por la especificidad de la experiencia en Sri Lanka como mezclada con el sufrimiento de la guerra y la política nacionalista tamil, sugiriendo por tanto que los procesos históricos y políticos son claves para entender las formas de pertenencia. Uso el lente de la capacidad de las deidades soberanas para esclarecer las diferentes formas empleadas por las deidades para atender las necesidades de los devotos. Exploro cómo las deidades hindúes y los devotos refugiados en Londres, mientras acomodan la política nacionalista, tratan de establecer su propio poder y afirmar una forma de pertenencia en el nuevo país. Argumento que, en el proceso tanto deidades soberanas nuevas como los refugiados/migrantes tamiles no solamente se necesitan el uno al otro sino también necesitan las deidades de su lugar de origen a través del tiempo y el espacio. [ política, religión, deidades soberanas, pertenencia, diáspora ] RÉSUMÉ: Cet article examine le rôle joué par les temples hindous dans la vie des tamouls de la diaspora sri lankaise au Royaume‐Uni. Il s'interroge sur les raisons pour lesquelles ces temples constituent non seulement des lieux de prière mais également des centres pour l'expression de visions nationalistes tamoules, tandis que les temples au Sri Lanka ont maintenu ces mêmes politiques à distance. Dans le cadre des études sur l'appartenance religieuse dans la diaspora, je soutiens la spécificité de l'expérience sri lankaise mêlée de souffrance due à la guerre et de politique nationaliste tamoule, suggérant ainsi l'importance des processus historiques et politiques dans la compréhension du sentiment d'appartenance. J'utilise la capacité des dieux souverains comme outil pour démêler les différentes méthodes utilisées par les dieux pour répondre aux besoins de leurs fidèles. J'explore la manière dont les dieux hindous et les fidèles réfugiés à Londres, tout en conciliant les politiques nationalistes, essaient d'établir leur propre pouvoir et revendiquent une forme d'appartenance dans le pays d'accueil. Je soutiens que dans le cadre de ce processus, les dieux souverains et les migrants/réfugiés tamouls ont besoin non seulement les uns des autres mais également des dieux du pays d'origine à travers le temps et l'espace. [ politique, religion, dieu souverain, appartenance, diaspora ]